Immediate Non-functional Loading of Single Tooth Uniti™ Implants into Avulsed Tooth Sockets Following Ridge Augmentation in the Anterior Maxilla: A Case Series - Vijayanathan, Radhakrishnan (Springer-Verlag, 2012)
To assess the clinical effectiveness of immediate non-functional loading of single-tooth implant placed into avulsed tooth socket following ridge augmentation in the anterior maxilla with bioglass bone substitute and biocollagen membrane. The clinical outcome of immediate non-functional loaded implants up to 24 months after placement into avulsed tooth sockets in anterior maxilla were evaluated in 15 patients. Implants were immediately restored with acrylic resin provisional crowns. Post-operative follow-up and intraoral radiographs were obtained at 6, 12, 18 and 24 months. Survival rate, implant threads exposure immediately after placement and at 6 month interval using CT 3D reconstruction was assessed. Marginal bone loss did not extend beyond the first thread and 3D CT scan showed adequate bone mineral density with no signs of radiolucent lesion around the implant during 24 months follow-up having survival rate of 100 %. Within the limits of the present study, immediate non-functional loading of single tooth implant placed into avulsed tooth socket following augmentation with bioglass bone substitute and biocollagen membrane in the anterior maxilla is one of the viable treatment alternatives for rehabilitation of immediate loading implant.